Multi-omics of extracellular vesicles: An integrative representation of functional mediators and perspectives on lung disease study - Liu, Yuexing; Li, Yixue; Zeng, Tao (Frontiers in Bioinformatics, 2023)
Extracellular vesicles (EVs) are secreted by almost all cell types. EVs include a broader component known as exosomes that participate in cell–cell and tissue–tissue communication via carrying diverse biological signals from one cell type or tissue to another. EVs play roles as communication messengers of the intercellular network to mediate different physiological activities or pathological changes. In particular, most EVs are natural carriers of functional cargo such as DNA, RNA, and proteins, and thus they are relevant to advancing personalized targeted therapies in clinical practice. For the application of EVs, novel bioinformatic models and methods based on high-throughput technologies and multi-omics data are required to provide a deeper understanding of their biological and biomedical characteristics. These include qualitative and quantitative representation for identifying cargo markers, local cellular communication inference for tracing the origin and production of EVs, and distant organ communication reconstruction for targeting the influential microenvironment and transferable activators. Thus, this perspective paper introduces EVs in the context of multi-omics and provides an integrative bioinformatic viewpoint of the state of current research on EVs and their applications.